2013
DOI: 10.4103/2230-8210.107822
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanisms, diagnosis and management of congenital hyperinsulinism

Abstract: Congenital hyperinsulinism (CHI) is the result of unregulated insulin secretion from the pancreatic β-cells leading to severe hypoglycaemia. In these patients it is important to make an accurate diagnosis and initiate the appropriate management so as to avoid hypoglycemic episodes and prevent the potentially associated complications like epilepsy, neurological impairment and cerebral palsy. At a genetic level abnormalities in eight different genes (ABCC8, KCNJ11, GLUD1, GCK, HADH, SLC16A1, HNF4A and UCP2) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…ob/ob mice demonstrated that the ablation of ghrelin improves the diabetic phenotype with increased insulin secretion, reduced blood glucose and improved glucose tolerance (6). Mitochondrial uncoupling protein 2 (UCP2) decreases ATP production to lower the ATP:ADP ratio, a key signal needed for insulin secretion (25). The ghrelin −/− .…”
Section: Introductionmentioning
confidence: 99%
“…ob/ob mice demonstrated that the ablation of ghrelin improves the diabetic phenotype with increased insulin secretion, reduced blood glucose and improved glucose tolerance (6). Mitochondrial uncoupling protein 2 (UCP2) decreases ATP production to lower the ATP:ADP ratio, a key signal needed for insulin secretion (25). The ghrelin −/− .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperinsulinemic hypoglycemia syndrome (HHS) is considered the most common cause of persistent hypoglycemia in infants and children 3, 4. To the authors' knowledge, HHS has not been previously reported as a distinct clinical entity in dogs.…”
Section: Casementioning
confidence: 99%
“…The clinical presentation of HH can be very heterogeneous ranging from very subtle presentation to severe disease needing pancreatectomy (2,3,4,5). It can be either permanent or transient; the permanent form is usually known as congenital.…”
Section: Introductionmentioning
confidence: 99%